The Field of Imagination : Thomas Paine and Eighteenth-Century Poetry - Cleary, Scott (Book collections on Project MUSE., 2019)
"The first book-length study of Thomas Paine as a poet, this book also examines his use of poetic epigraphs, his image in eighteenth-century political poetry, and his influence on later American poets"--